From «weakening of state» to «builing of state»: theoretical sharp turn - L. A. Gaynutdinova (Aspekti Publìčnogo Upravlìnnâ, 2015)
Today we can state that neoliberal globalization having broken national identity and sovereignty, didn’t establish any adequate structure that can catch prerogatives that are slipping away from national states and societies and cannot focus them on wider geopolitical area. Though in the conditions of radicalization of competition on the world stage and with respect to threats that appear from no control in the world there appear new growing-points for development. This exact fact dictated a sharp turn of attention from the theory of ‘Weakening of State’ to the theory of ‘Building of State’.